Fully resorbable poly-4-hydroxybutyrate (P4HB) mesh for soft tissue repair and reconstruction: A scoping review - Deeken, Corey R.; Chen, David C.; Lopez-Cano, Manuel; Martin, David P.; Badhwar, Amit (Frontiers in Surgery, 2023)
Background Poly-4-hydroxybutyrate (P4HB) is a fully resorbable, biologically-produced polymer with a strength and flexibility comparable to permanent synthetic polymers. The objective was to identify/summarize all peer-reviewed publications involving P4HB mesh. Methods A scoping review was conducted within PubMed and included articles published through October 2022. Results A total of n = 79 studies were identified (n = 12 in vitro/bench; n = 14 preclinical; n = 6 commentaries; n = 50 clinical). Of the clinical studies, n = 40 reported results applicable to hernia and n = 10 to plastic/reconstructive surgery and involved patients of all Centers for Disease Control (CDC) wound classes and Ventral Hernia Working Group (VHWG) grades. Conclusion P4HB mesh provides long-term hernia repair strength and exhibits promising clinical outcomes beyond its resorption period. Future studies should include randomized controlled trials comparing P4HB to other biomaterials, as well as optimal patient selection, operative technique, long-term outcomes, minimization of potential mesh-related complications, and potential contraindications/complications for P4HB in hernia/abdominal wall reconstruction.